PERSEPSI MASYARAKAT TENTANG PEMBANGUNAN JALAN DI KENAGARIAN RANTAU LIMAU KAPAS KECAMATAN SANGIR BATANG HARI KABUPATEN SOLOK SELATAN - Marnis, Ega - (Pendidikan Geografi, 2014)
This study aims to identify and analyze about the public perception of the construction of roads in Rantau Kenagarian Lemons Cotton. The research is a qualitative research. The informants diamabil in purposive sampling is a technique of data collection with particular consideration. The selection of informants was done by prior research should know that the people who will be selected to provide the desired information. Informants in this study is a community that is on the side of the road construction. The results of research in the field: 1) Public perception of road construction, changes in terms of the means of transport used to wear boat (tempek) now use the car and the cost is also efficient and fast does not take a long time to have the construction of a road to connect to the Sar instance to the district and the city center. 2) Construction of roads provides an opportunity to open a shop for people Rantau Lemons Quilts and generate revenue that can meet their basic needs for everyday. 3) The public perception that the community is important interactions among each other admonish admonished fellow neighbors, fellow community and immigrants alike. 4) Security was us who created both environmental safety, child safety, our security on the way, the importance of a sense of community awareness of each other and remind each other in life community